Foundations of the World republic - "Borgese, G. A." (Chicago, 1953)
Reader will find in this strange and wonderful book a creation, wide-arched soaring, of idea and form . A mind of power and passion has built here a new kind of structure of thought and words about old, tremendous questions. Here problems of political action are expressed and resolved in metaphysical speculation, and both are lifted on wings of poetry
Keywords: Political science